Intervening Fatigue Program on Fatigue, Self-Esteem, Body Image, Life Quality on Breast Cancer Survivors - Dwi Prihatin Era; Ratna Sitorus; Yati Afiyanti; Tris Eryando (Indonesian Journal of Multidisciplinary Science, 2022)
The incidence of breast cancer in Indonesia is the highest among other cancers in women, with an estimated prevalence of fatigue between 25-99%. The current study is a 6-week mixed methods action study on fatigue in breast cancer patients. This study aimed to develop a self-management intervention program to reduce empowerment-based fatigue with telenursing strategies and to seek evidence of its effect on fatigue levels, self-esteem, body image, and quality of life. The first stage describes the problem with a qualitative method by exploring the fatigue problem in the survivor's perception. The second stage is the intervention development stage, and the third stage is testing the effectiveness of the intervention, carried out in a quasi-experimental study with a pre-posttest control group design. The first stage produces five themes, and the second stage produces nursing interventions based on transitional nursing theory and telenursing strategies. The third stage of the study proved that the fatigue management intervention (IPK) effectively reduced fatigue levels, increased self-esteem and body image, and improved the quality of life in breast cancer patients. This study recommends oncology nurses consider empowering survivors using this intervention so that the transition period for breast cancer survivors achieves healthy physical and psychological health, achieving optimal health after a cancer diagnosis.